An Introduction to Modern Political Theory - Barry, Norman P. author. aut Link
XVIII, 309 p.
Keywords: This student textbook introduces the concept of political theory from various viewpoints, such as justice and the law, government and the state, and equality and human rights. It analyzes the concepts of power, liberty and a series of political principles.